To Correlate D-dimer Levels with disease severity of seropositive Rheumatoid Arthritis according to CDAI (Clinical Disease Activity Index) and DAS 28-CRP score - Dr. Anmol Sahoo, Dr. S. Kabi, Dr. L.K. Meher, Dr. Samir Sahu, Dr. Samir Jena, Dr. Nikta (South Eastern European Journal of Public Health, 2025)
Background: Rheumatoid Arthritis (RA) is characterized by chronic inflammation and altered coagulation parameters. While D-dimer has emerged as a potential marker of inflammation, its relationship with standardized disease activity measures in RA remains incompletely understood. This study investigated the correlation between D-dimer levels and disease severity in seropositive RA patients using validated clinical indices. Methods: In this cross-sectional study, 100 seropositive RA patients were evaluated. Disease activity was assessed using the Clinical Disease Activity Index (CDAI) and Disease Activity Score 28-CRP (DAS28-CRP). D-dimer levels were measured using quantitative immunoturbidimetric assay. Correlations between D-dimer levels and disease activity scores were analyzed, and D-dimer levels were compared across different disease activity categories. Results: The study population (mean age 52.3 ± 12.7 years, 78% female) showed significant correlations between D-dimer levels and both CDAI (rs=0.685, p<0.001) and DAS28-CRP scores (rs=0.692, p<0.001). Median D-dimer levels progressively increased across disease activity categories from remission (0.34 μg/mL) to high disease activity (1.25 μg/mL) for CDAI, with similar patterns observed for DAS28-CRP categories. Significant correlations were also found between D-dimer levels and traditional inflammatory markers (ESR: rs=0.542, CRP: rs=0.568, p<0.001) as well as autoantibody titers (RF: rs=0.412, anti-CCP: rs=0.398, p<0.001). Conclusion: D-dimer levels demonstrate strong correlation with disease activity in seropositive RA, suggesting its potential utility as an additional marker for disease severity assessment. The progressive increase in D-dimer levels with increasing disease activity supports its role in reflecting the inflammatory burden in RA. These findings contribute to our understanding of the relationship between inflammation and coagulation activation in RA, with potential implications for disease monitoring and risk stratification.